2017
DOI: 10.1007/s10787-017-0337-0
|View full text |Cite
|
Sign up to set email alerts
|

The impact of mangiferin from Belamcanda chinensis on experimental colitis in rats

Abstract: BackgroundInflammatory bowel disease (IBD) [including Crohn’s disease (CD) and ulcerative colitis (UC)] constitutes an important clinical problem. The pathogenesis of IBD remains unclear. It is believed that immune dysfunction, inflammatory mediators and oxidative damage play crucial roles in development of IBD. The condition is clinically associated with symptoms ranging from mild to severe during relapses, depending on the affected segment of the gastrointestinal tract. Bloody diarrhea with mucus, abdominal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 19 publications
0
28
0
Order By: Relevance
“…MG has been shown to exert various biological activities and therapeutic effects, including anti-inflammatory [7], anti-oxidative [8], anti-tumor [9] and anti-diabetic effects [10] as well as regulation of metabolism [11]. Recent studies have demonstrated that MG attenuates inflammation in experimental colitis [12], corrects the imbalance of Th17/Treg cells in mice with TNBSinduced colitis [13] and inhibits macrophage activation. Therefore, we hypothesized that MG may be effective in treating LN via induction of Tregs.…”
Section: Introductionmentioning
confidence: 99%
“…MG has been shown to exert various biological activities and therapeutic effects, including anti-inflammatory [7], anti-oxidative [8], anti-tumor [9] and anti-diabetic effects [10] as well as regulation of metabolism [11]. Recent studies have demonstrated that MG attenuates inflammation in experimental colitis [12], corrects the imbalance of Th17/Treg cells in mice with TNBSinduced colitis [13] and inhibits macrophage activation. Therefore, we hypothesized that MG may be effective in treating LN via induction of Tregs.…”
Section: Introductionmentioning
confidence: 99%
“…78 Overproduction of ROS in intestinal mucosal cells induces the immune response, which leads to the injury of intestinal epithelial cells, disruption of integrity of the intestinal barrier, and initiation of the intestinal inflammation. 79 It is involved in anti-inflammation process and cleared by a series of constitutively expressed antioxidant enzymes, such as SOD and GSH-Px. These two enzymes can counteract the overaccumulation of ROS.…”
Section: Figurementioning
confidence: 99%
“…[14,15]. It has shown many kinds of biological activities and pharmacological actions such as antioxidative, antidiabetic, hypolipidemic, antiviral, immunomodulatory, anticancer, analgesic and hepatoprotective effects [16][17][18][19][20]. But the characteristic of its low aqueous solubility and low fat solubility can affect the absorption process of drugs in vivo, which leads to a low bioavailability [21,22].…”
Section: Introductionmentioning
confidence: 99%